Mineral constituents of conserved white button mushrooms: similarities and differences - Sviatlana Pankavec; Anetta Hanć; Danuta Barałkiewicz; Anna Dryżałowska; Ji Zhang; Jerzy Falandysz (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. Mushrooms are a food that is often considered as an important source of minerals and other nutrients for consumers. There is little data on the minerals in mushrooms processed culinary and on the impact of processing. Objective. The research was aimed at understanding the similarities and differences in the mineral composition (Hg, Li, Mg, Al, Co, Ni, Cu, As, Se, Rb, Sr, Ag, Cd, Cs, Sb, Tl, Pb, U, Ba, Cr, Zn, Mn and V) of white button mushrooms (Agaricus bisporus) processed in industrial conditions. Material and methods. Fungal materials came from six producers. The elements were determined by ICP-MS DRC and CV-AAS using validated methods and QA/QC protocol. The interdependencies of 18 elements and 10 batches of mushrooms examined were tested with the help of principal component analysis. Results. Some significant differences were found in the content and composition of minerals in marinated white button mushrooms depending on producer. Conserved white button mushrooms are poorer in major essential elements but also in toxic Hg, As, Ag, Cd, Sb, Tl or Pb which has been reported for unprocessed mushrooms. Conclusions. The relatively higher levels of Ag in some batches seem to be largely explained by the quality of the substrate used for mushrooms cultivation, while of Li, Rb, Cs, Cr, Al, U, V, As and Mn (in part also of Ba and Sr) largely by the quality of the marinade.